Impaired glucose tolerance and insulin resistance are associated with increased adipose 11beta-hydroxysteroid dehydrogenase type 1 expression and elevated hepatic 5alpha-reductase activity. - Tomlinson, J; Finney, J; Gay, C; Hughes, B; Hughes, S; Stewart, P (2008)
OBJECTIVE: The precise molecular mechanisms contributing to the development of insulin resistance, impaired glucose tolerance (IGT), and type 2 diabetes are largely unknown. Altered endogenous glucocorticoid metabolism, including 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1), which generates active cortisol from cortisone, and 5alpha-reductase (5alphaR), which inactivates cortisol, has been implicated. RESEARCH DESIGN AND METHODS: A total of 101 obese patients (mean age 48 +/- 7 years, BMI 34.4 +/- 4.3 kg/m(2), 66 women, 35 men) underwent 75-g oral glucose tolerance testing (OGTT), body composition analysis (dual-energy X-ray absorptiometry), assessment of glucocorticoid metabolism (24-h urine steroid metabolite analysis by gas chromatography/mass spectrometry), and subcutaneous abdominal adipose tissue biopsies. RESULTS: A total of 22.7% of women had IGT compared with 34.2% of men. Two women and five men were diagnosed with type 2 diabetes. In women, adipose 11beta-HSD1 expression was increased in patients with IGT and correlated with glucose levels across the OGTT (R = 0.44, P < 0.001) but was independent of fat mass. Total glucocorticoid secretion was higher in men with and without IGT (normal 13,743 +/- 863 vs. 7,453 +/- 469 microg/24 h, P < 0.001; IGT 16,871 +/- 2,113 vs. 10,133 +/- 1,488 microg/24 h, P < 0.05), and in women, it was higher in those with IGT (7,453 +/- 469 vs. 10,133 +/- 1,488 microg/24 h, P < 0.001). In both sexes, 5alphaR activity correlated with fasting insulin (men R = 0.53, P = 0.003; women R = 0.33, P = 0.02), insulin secretion across an OGTT (men R = 0.46, P = 0.01; women R = 0.40, P = 0.004), and homeostasis model assessment of insulin resistance (men R = 0.52, P = 0.004; women R = 0.33, P = 0.02). CONCLUSIONS: Increased adipose 11beta-HSD1 expression in women may contribute to glucose intolerance. Enhanced 5alphaR activity in both sexes is associated with insulin resistance but not body composition. Augmented glucocorticoid inactivation may serve as a compensatory, protective mechanism to preserve insulin sensitivity.